In vitro sensitivity testing of Cladobotryum mycophilum to carbendazim and prochloraz manganese - Chakwiya, Alinesi; van der Linde, Elna J.; Korsten, Lise (South African Journal of Science, 2015)
Limited information of fungicide efficacy on cultivated mushrooms and resistance development potential is available. Minor crop industries in general have a smaller arsenal of protectants to rely on and the likelihood of resistance build-up is of greater concern. This study focused on Cladobotryum mycophilum's sensitivity to carbendazim and prochloraz manganese following recent reports on decreased efficacy of both fungicides. The median effective dose (ED50) values for carbendazim ranged between 0.02 mg/L and 4.31 mg/L with 60% of the South African isolates being moderately resistant. The highest resistance factor for carbendazim was 215. Prochloraz manganese ED50 values varied from 0.00001 mg/L to 0.55 mg/L. A significant difference in mean ED50 values for both fungicides tested was observed. Using cluster analysis, no discrimination of isolates previously exposed and unexposed to prochloraz manganese was observed. A wide range of differences in ED50 values indicated moderate resistance to carbendazim and high sensitivity to prochloraz manganese among isolates under investigation. Discriminant analysis indicated significant differences between clusters contributed by one or a few variables. This study provided evidence that prochloraz manganese remains highly fungitoxic to C. mycophilum. However, prochloraz manganese is to be used in a disease management strategy in combination with strict farm hygiene management strategies to retain product efficacy and ensure crop protection.